The effects of silazapril and atenolol on the cıırdiov ııscıı hır and endocrine responses to anesthesia induetion and endotracheal intubation (Annals of Medical Research, 2021)
None
Keywords: s : ACE inhibitors, silazapril, beta blockers, atenolol, stress response